Conceptual Framework on Antecedents of True and Fair View Reporting Surrounding Migration to Accrual-Based Accounting by Public Sector Entities: A Case of Federal Statutory Bodies (FSB) in Malaysia - Muhammad Aiman Asyraf Hanafi; Norzarina Md Yatim; Abdullah Sallehhuddin Abdullah Salim (Information Management and Business Review, 2023)
Following the institutional reforms in Malaysia, the Federal Government issued Treasury Circular PS 1.2/2020. Federal Statutory Bodies (FSBs) are now required to adopt the Malaysian Public Sector Accounting Standard (MPSAS) as the standard for preparing financial statements. While most private sectors strongly embrace accrual accounting systems and derive many benefits from them, the practice and application in the public sector, including FSBs, is still in its infancy. Therefore, this study examines the antecedents of true and fair view reporting in the context of migration to accrual accounting by FSB in Malaysia. This study is due to the lack of research on accrual accounting in the public sector, as researchers rigorously focus on the private sector that controls the economy. In addition, there are few studies on the conversion of the public sector in emerging economies to accrual accounting. The study provided a conceptual discussion on the antecedents that potentially affect the true and fair view reporting through the adoption of accrual accounting. The discussion is expected to benefit many stakeholders, especially regulators and policymakers, as emerging economies such as Malaysia continue to actively pursue institutional reforms. By adding new variables from the study so that they can be used in various and extensive aspects of the research.